2023
DOI: 10.1186/s12866-023-02916-8
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen availability and pH variation in a medium simulating vaginal fluid influence the growth of vaginal Lactobacillus species and Gardnerella vaginalis

Abstract: Background Glycogen metabolism by Lactobacillus spp. that dominate the healthy vaginal microbiome contributes to a low vaginal pH (3.5–4.5). During bacterial vaginosis (BV), strict and facultative anaerobes including Gardnerella vaginalis become predominant, leading to an increase in the vaginal pH (> 4.5). BV enhances the risk of obstetrical complications, acquisition of sexually transmitted infections, and cervical cancer. Factors critical for the maintenance of the healthy vaginal microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…As MRSB does not support the growth of Gardnerella spp. [51], we resuspended the retentates recovered from 10 kDa MWCO columns (fLj-MRSB-CFS24 and fMRSB) in NYCB and added them to additional NYCB (1 : 6 v/v) inoculated with Gp JCP8151B. As expected, the fMRSB (retentate resuspended in NCYB) did not support further growth of Gp JCP8151B; at 24 hpi, the initial inoculum was reduced by one log but not eliminated ().…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…As MRSB does not support the growth of Gardnerella spp. [51], we resuspended the retentates recovered from 10 kDa MWCO columns (fLj-MRSB-CFS24 and fMRSB) in NYCB and added them to additional NYCB (1 : 6 v/v) inoculated with Gp JCP8151B. As expected, the fMRSB (retentate resuspended in NCYB) did not support further growth of Gp JCP8151B; at 24 hpi, the initial inoculum was reduced by one log but not eliminated ().…”
Section: Resultsmentioning
confidence: 91%
“…Since the greatest reduction in c.f.u. occurred in the Gp JCP8151B-Lj 62B co-culture (), and since we had previously found that the growth of Lj 62B was more robust in MSVF at pH 5.0 [51], we continued our analyses using Lj 62B. To investigate this phenomenon further, and to determine if this effect might occur at an earlier time point during the co-culturing, we repeated the experiment but obtained samples at 16, 20, 22, and 24 hpi.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations